ROLE OF THE NOTCH1 GENE IN FORMATION OF AORTIC ANEURYSM - O. V. Irtyuga; O. A. Freilichman; D. S. Krivonosov; A. B. Malashicheva; S. I. Tarnovskaya; V. Е. Uspenskiy; M. L. Gordeev; O. P. Rotar; A. A. Kostareva; O. M. Moiseeva (Российский кардиологический журнал, 2018)
Aim. To evaluate the impact of genetics in development of thoracic aneurysm in patients with tricuspid valve (TAV) and bicuspid aortic valve (BAV) based on the analysis and search for mutations in NOTCH1.Material and methods. In the study, 60 patients included with the dilation of thoracic aorta more than 40 mm and 200 patients with no aortic pathology, included in the comparison group. All patients underwent echocardiographic assessment on Vivid 7 (GE, USA) equipment, by standard protocol. For molecular genetics we utilized the strategy of targeted mutation screening, including the analysis of 10 of 34 exones of the gene NOTCH1, performed with the direct sequencing.Results. Patients with BAV were younger than those with no inborn defect. Arterial hypertension was verified only in every second BAV patient. Also, maximal rates of blood pressure were significantly lower in patients with inborn defects (р<0,02). As a result of genetic analysis in the studied group, in 9 patients with inborn defect and 2 patients with TAV there were 10 variants found of aminoacid replacement in 6 among 10 analyzed exones, of those 5 replacements — synonimic, and the mutation S2449R was found first time. Mutations P1227S, E1305K, R1279H and D1267N were found at the site of Notch1 protein binding with DLL4, of those 3 are highly pathogenic, that could influence the protein-protein interactions Notch1 with DLL4 leading to formation on aneurysm.Conclusion. Mutations P1227S D1267, E1305K in the gene NOTCH1, being highly pathogenic, may lead to the changes of protein functioning via Notch signalling disorder, that is more characteristic for BAV patients.